2012
DOI: 10.1002/chir.22024
|View full text |Cite
|
Sign up to set email alerts
|

Chiral recognition of metalaxyl enantiomers by human serum albumin: evidence from molecular modeling and photophysical approach

Abstract: Metalaxyl is an acylamine fungicide, belonging to the most widely known member of the amide group. This task is aimed to scrutinize binding region and spatial structural change of principal vector human serum albumin (HSA) complex with (R)-/(S)-metalaxyl by exploiting molecular modeling, steady-state and time-resolved fluorescence, and circular dichroism (CD) approaches. According to molecular modeling, (R)-metalaxyl is situated within subdomains IIA and IIIA and the affinity of site I with (R)-metalaxyl is gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…There are several areas of concern that need to be extensively investigated. These chemicals are widely used in industry, agriculture, home and gardens for many different purposes, including the protection of seed grain during storage and germination [10]. Individuals who are exposed to these chemicals include agricultural workers, those living in proximity to farms/orchards or consumers who are exposed to pesticide residues in food [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several areas of concern that need to be extensively investigated. These chemicals are widely used in industry, agriculture, home and gardens for many different purposes, including the protection of seed grain during storage and germination [10]. Individuals who are exposed to these chemicals include agricultural workers, those living in proximity to farms/orchards or consumers who are exposed to pesticide residues in food [5].…”
Section: Introductionmentioning
confidence: 99%
“…Metalaxyl is a systemic benzenoid fungicide belonging to the most widely known member of the amide group. It is used in foliar spray mixtures for tropical and subtropical crops, as a soil treatment for the control of soil-borne pathogens, and as a seed treatment to control downy mildews, fungal diseases on fruits, cotton, soybeans, peanuts, ornamentals and grasses [10]. Metalaxyl is reported to have hazardous effects on mammalian animals [39].…”
Section: Introductionmentioning
confidence: 99%
“…The problems resulting from metalaxyl come from their high residual level in agriculture crops especially vegetables cultivated under greenhouse conditions and doi: 10.7243/2055-091X- [2][3][4][5][6][7][8][9] found that imidaclopride and metalaxyl have genotoxic effects as they induced micronucleus formation in human lymphocytes in vitro and in polychromatic erythrocytes of the rat's bone marrow in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, increasing more attention was paid on the molecular mechanisms involved in enantioselective discrimination by HSA. For instance, investigations have shown that enantiomers of warfarin, catechin, ketoprofen, ibuprofen and metalaxyl behave significantly different in pharmacokinetics and interaction with HSA [10][11][12][13][14]. As mentioned above, enantioselectivity in protein binding assessment is a momentous part in the biodistribution of chiral ligands, whereas such consequences cannot be obtained from achiral analysis.…”
Section: Introductionmentioning
confidence: 93%
“…Peeples et al [31] have investigated the binding of organophosphorus pesticides to commercial albumin protein and indicated there was less physiologically relevant pesticide binding to albumin. Ding et al [13] explored the enantioselective binding of metalaxyl enantiomers to HSA, indicating the binding affinity and binding sites were different between enantiomers. Fig.…”
Section: Analysis Of Fluorescence Quenching Of Hsa By Dm Enantiomersmentioning
confidence: 99%